Propriedades estruturais e magnéticas das ligas Heusler Cu50Mn(50-x)Inx - Andrez, Jhone Ramsay (2013)
In this work, we have investigated the magneto-structural properties of the Cu50Mn(50-x)Inx (x = 10, 14, 15, 16, 18, 20, 22,5 e 25) Heusler-type alloys. The studied samples were prepared by arc-melting furnace and were annealed at 835 K for 4 days in a evacuated quartz tube. X-ray diffraction (XRD), recorded at room temperature, was used to determine the sample crystalline structures. Magnetic properties were recorded by both VSM and a modified TG-A (thermogravimetric analysis) adapted to determine magnetic transitions using a permanent magnet. DSC was also applied to get information from the structural transition temperatures (first order phase features). From VSM method, it was measured DC magnetization as a function of applied magnetic field [M(H)] and temperature [M(T)], while with thermogravimetric analysis it was checked the temperature dependence of the magnetic transition temperatures (TC) and compare with VSM method. X-rays data have shown that the samples with 10 = x = 16 are stabilized with a mixture of a martensitic and austenitic (L21) structures. For the In interval 18 = x = 25, the samples have L21-type crystalline structure (single phases). From the M(T) curves, it was observed a continuous reduction of TC by replacing Mn atoms by In at the interval 18 = x = 25. Due to a presence of two crystalline phases for In concentration range 14 = x = 16, two magnetic transition temperatures, associated with the austenitic and martensitic phases, were defined. For the sample with x = 10, only one magnetic transition temperature is detected and it was associated with the martensitic phase seen by XRD. No first order phase transitions were observed by DSC measurements at the temperature interval 300-600 K for the studied samples. The M(H) curves collected at different temperatures and for maximum field of 5 T indicate that the studied samples have a conventional soft ferromagnetic behavior, with low coercive field and high saturation magnetization at low fields